2007
DOI: 10.1161/01.res.0000260250.83824.8f
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Endocytic Recycling of KCNQ1/KCNE1 Potassium Channels

Abstract: Abstract-Stress-dependent regulation of cardiac action potential duration is mediated by the sympathetic nervous system and the hypothalamic-pituitary-adrenal axis. It is accompanied by an increased magnitude of the slow outward potassium ion current, I Ks . KCNQ1 and KCNE1 subunits coassemble to form the I Ks channel. Mutations in either subunit cause long QT syndrome, an inherited cardiac arrhythmia associated with an increased risk of sudden cardiac death.Here we demonstrate that exocytosis of KCNQ1 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
154
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 36 publications
6
154
2
Order By: Relevance
“…For the latter pathway, it has been reported that SGK phosphorylates and stimulates PIKfyve, a FYVE finger-containing phosphoinositide kinase that acts on phosphatidylinositol 3-phosphate to generate PI(3,5)P 2 (35). SGK-mediated activation of PIKfyve as well as addition of PI(3,5)P 2 to the cell have been shown to positively regulate Rab11-mediated insertion of KCNQ1/KCNE1 channels to the membrane (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the latter pathway, it has been reported that SGK phosphorylates and stimulates PIKfyve, a FYVE finger-containing phosphoinositide kinase that acts on phosphatidylinositol 3-phosphate to generate PI(3,5)P 2 (35). SGK-mediated activation of PIKfyve as well as addition of PI(3,5)P 2 to the cell have been shown to positively regulate Rab11-mediated insertion of KCNQ1/KCNE1 channels to the membrane (16).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is Rab11, which is highly expressed in cardiac myocytes (28) and is involved in the recycling/trafficking of various ion channels such as cystic fibrosis transmembrane conductance regulator chloride channels, Cav1.2 Ca 2ϩ channels, and the glucose transporter GluT4 (28 -30). In particular, SGK1 has been shown to increase the expression of the KCNQ1/KCNE1 (I Ks ) channel in the plasma membrane, and this increase is via the activation of a Rab11-mediated pathway (16).…”
Section: Volume 288 • Number 21 • May 24 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…Endocytosis motifs in intracellular loops could have relevance to other multipass membrane proteins that undergo endocytosis, such as ion channels and G protein-coupled receptors (26,27). Whereas cytoplasmic tails can be readily inserted into chimeric reporter proteins for detailed analysis of endocytosis motifs (23), analyses of intracellular loops in isolation of the remainder of the membrane protein are more problematic because the structures of the intracellular loops are likely to be dependent on the correct membrane topology.…”
Section: Discussionmentioning
confidence: 99%
“…49 AQP2 is retrieved to early endosomes, and then transferred back to the Rab11-positive storage compartment. Thus, interference with Rab11 function might have unforeseen consequences, perturbing airway hindrance due to off-target effects on channels like AQP2 or potassium channels such as the potassiumvoltage-gated subfamily Q member 1 (KCNQ1) 50 or the voltage-dependent Kv1.5 51 whose recycling is also mediated by Rab11. Interestingly, a recent study described the cholesterol-lowering drugs statins, as potential potentiators of vasopressin-independent trafficking of AQP2 channels in the kidney.…”
Section: Rab Proteins As Putative Therapeutic Targetsmentioning
confidence: 99%